A high-strength carbon fiber synchronous belt and preparation method thereof
By combining high-hardness hydrogenated nitrile glue and modified carbon fiber rope, the problem of insufficient heat resistance during high-speed operation is solved, and higher mechanical and mechanical properties and longer service life are achieved.
Patent Information
- Application Number
- CN202410920055.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-10
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-07-10
AI Technical Summary
The existing synchronous belts are too high when operating at high speed, and the material has insufficient heat resistance, resulting in insufficient lifespan, and problems such as wear, insufficient strength and poor cold resistance.
High-hardness hydrogenated nitrile glue is used as the main material for the synchronization tape film, and combined with blended materials such as ethylene propylene fluoride rubber, ethylene acrylate rubber, etc., a modified carbon fiber rope is used as a skeleton to form an adhesive-modified carbon fiber synchronization tape. This method forms an interpenetrating network structure and Fuker reaction through the action of a vulcanizing agent and a catalyst, thereby improving cross-linking density and performance stability.
It significantly improves the mechanical and mechanical properties, wear resistance, heat aging resistance and cold resistance of the synchronization belt, extends the service life, and reduces production costs and energy consumption.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of synchronous belt transmission and conveying, and in particular to a high-strength carbon fiber synchronous belt and a preparation method thereof. Background Art
[0002] The synchronous belt is an annular belt with equally spaced teeth on the inner surface. When it rotates, the belt teeth and the tooth grooves of the gears are meshed to transmit power. The synchronous belt combines the advantages of belt drive, chain drive and gear drive. It has the advantages of high transmission efficiency, accurate transmission ratio, wide transmission ratio range, stable transmission, small force on the shaft, low noise and energy saving.
[0003] The existing synchronous belts generally have a short lifespan, mainly because the temperature is too high under high-speed operation, and the heat resistance of the corresponding materials needs to be improved. Synchronous belts will inevitably wear out after a period of use, and have technical defects such as insufficient strength and poor cold resistance.
[0004] Carbon fiber is a fiber material with excellent specific strength and stiffness, low thermal expansion, high modulus, high wear resistance, corrosion resistance and other advantages. It is widely used in aviation, transportation, batteries, sports goods and other fields. In recent years, in order to improve the performance of synchronous belts, the reinforcement skeleton of synchronous belts is mostly composed of carbon fiber twisted ropes, but the surface of carbon fiber is chemically inert, amphiphobic, and smooth, and it is poorly impregnated with rubber resins and the like and it is difficult to form a strong interaction, resulting in unsatisfactory interface performance between the rope and the rubber matrix, and ultimately causing the performance of the synchronous belt to fail to meet expectations.
[0005] In order to solve the above problems, a Chinese invention patent with the authorization announcement number CN116262848B discloses a high-performance carbon fiber synchronous belt and a preparation method thereof. The high-performance carbon fiber synchronous belt comprises a skeleton, a main body rubber and a wrapping cloth attached to the outside of the skeleton, wherein the main body rubber is a high-hardness hydrogenated nitrile rubber, and the high-hardness hydrogenated nitrile rubber contains the following components: eugenol and perfluorooctyl ethyl acrylate modified HNBR, carbon black and additives. The use of high-hardness hydrogenated nitrile rubber can improve the strength and high-temperature resistance of the synchronous belt, and the layers of the synchronous belt can be compounded together using general rubber belt equipment. The invention also provides a preparation method for the high-performance carbon fiber synchronous belt, firstly mixing the components of the high-hardness hydrogenated nitrile rubber to obtain the high-hardness hydrogenated nitrile rubber; then combining the skeleton, the main body rubber and the wrapping cloth, and vulcanizing to obtain the synchronous belt. However, the wear resistance, heat aging resistance and cold resistance of the synchronous belt still need to be further improved, and the compatibility between the skeleton and the rubber material needs to be further improved.
[0006] It can be seen that the development of a high-strength carbon fiber synchronous belt with good mechanical properties, excellent wear resistance, heat aging resistance and cold resistance, good performance stability and long service life and its preparation method meet market demand, have broad market value and application prospects, and are of great significance to promoting the development of the synchronous belt field. Summary of the invention
[0007] The main purpose of the present invention is to provide a high-strength carbon fiber synchronous belt with good mechanical properties, excellent wear resistance, heat aging resistance and cold resistance, good performance stability and long service life, and a preparation method thereof.
[0008] To achieve the above purpose, the present invention provides a high-strength carbon fiber synchronous belt, comprising a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 30-40 parts of hydrogenated nitrile rubber, 10-20 parts of ethylene acrylate rubber, 20-30 parts of fluorinated ethylene propylene rubber, 1-3 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 2-4 parts of bis(1-vinyl imidazole-2-)ketone, and 3-5 parts of 2,4,6-trivinyl cycloboroxane. , 2-4 parts of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2-5 parts of N-vinylcarbazole, 1-2 parts of 4,4-chloroformylphenyl ether, 0.3-0.5 parts of catalyst, 3-5 parts of coupling agent, 10-20 parts of inorganic filler, 1-3 parts of stearic acid, 1-3 parts of antioxidant, 2-4 parts of vulcanizing agent, 0.3-0.5 parts of scorch retarder, and 2-4 parts of waste polyaromatic oxadiazole fiber; the synchronous belt skeleton is a binder-modified carbon fiber cord.
[0009] Preferably, the waste polyaromatic oxadiazole fibers are recycled from waste Baodelun materials provided by Jiangsu Baode New Materials Co., Ltd.; the average diameter of the waste polyaromatic oxadiazole fibers is 3-9 μm, and the aspect ratio is (15-25):1.
[0010] Preferably, the anti-scorch agent is anti-scorch agent CTP.
[0011] Preferably, the vulcanizing agent is a mixture of benzoyl peroxide, di-tert-butyl peroxide, and dicumyl peroxide in a mass ratio of 1:(1-2):(0.8-1.2).
[0012] Preferably, the antioxidant is at least one of antioxidant NBC and antioxidant BLE.
[0013] Preferably, the inorganic filler is a mixture of white carbon black, light calcium carbonate and graphene oxide in a mass ratio of 1:(0.8-1.2):(1-2); the particle size of the inorganic filler is 1000-1500 mesh.
[0014] Preferably, the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570; and the catalyst is a mixture of anhydrous ferric chloride and anhydrous zinc chloride in a mass ratio of (1-2):1.
[0015] Preferably, the hydrogenated nitrile rubber is selected from the group consisting of ® The hydrogenated nitrile rubber raw rubber of ZN35156; the ethylene acrylate rubber is selected from the brand Vamac produced by DuPont Company of the United States ® DP ethylene acrylate rubber raw rubber; the fluorinated ethylene propylene rubber is selected from the brand AFLAS ® 150% fluorinated EPDM raw rubber.
[0016] Preferably, the method for preparing the binder-modified carbon fiber cord comprises the following steps: immersing the carbon fiber cord in a binder solution for 1-3 hours, taking it out and drying it to obtain the binder-modified carbon fiber cord.
[0017] Preferably, the binder solution is an ethanol solution of silane coupling agent KH550 with a mass percentage concentration of 3-6%.
[0018] Another object of the present invention is to provide a method for preparing the high-strength carbon fiber synchronous belt, comprising the following steps:
[0019] Step S1, putting hydrogenated nitrile rubber, ethylene acrylate rubber and fluorinated ethylene propylene rubber into an open mill for mixing, alternately adding other raw materials, and mixing evenly to obtain a synchronous belt film;
[0020] Step S2, pasting the synchronous belt film package on the synchronous belt frame, and then placing it in a synchronous belt mold for compression molding and vulcanization, and cooling to room temperature to obtain a high-strength carbon fiber synchronous belt.
[0021] Preferably, in step S2, the vulcanization temperature is 160-170° C., the vulcanization pressure is 10-15 MPa, and the vulcanization time is 30-40 min.
[0022] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0023] (1) The method for preparing the high-strength carbon fiber synchronous belt disclosed in the present invention does not require special equipment or improvement of the existing production line. It has low capital investment, low energy consumption, simple process, convenient operation and control, high preparation efficiency and finished product qualification rate, is suitable for continuous large-scale production, and has high promotion and application value.
[0024] (2) The high-strength carbon fiber synchronous belt disclosed in the present invention comprises a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 30-40 parts of hydrogenated nitrile rubber, 10-20 parts of ethylene acrylate rubber, 20-30 parts of fluorinated ethylene propylene rubber, 1-3 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 2-4 parts of bis(1-vinylimidazole-2-)ketone, 3-5 parts of 2,4,6-trivinylcycloboroxane, 2-4 parts of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2-5 parts of N-vinyl carbazole, 1-2 parts of 4,4-chloroformylphenyl ether, 0.3-0.5 parts of a catalyst, 3-5 parts of a coupling agent, and an inorganic filler. 10-20 parts, 1-3 parts of stearic acid, 1-3 parts of antioxidant, 2-4 parts of vulcanizing agent, 0.3-0.5 parts of anti-scorch agent, 2-4 parts of waste polyaromatic oxadiazole fiber; hydrogenated nitrile rubber, ethylene acrylate rubber, fluorinated ethylene propylene rubber are blended as the base material, and their respective advantages are combined to make the manufactured high-strength carbon fiber synchronous belt have good mechanical properties, excellent wear resistance, heat aging resistance and cold resistance, good performance stability and long service life; through the mutual cooperation between the components of the film preparation raw materials, perfluoropropane, phenyl, imidazolinone, cycloboroxane, triazone, carbazole and phenyl ether structures are simultaneously introduced into the film structure, and these structures, under the multiple effects of electronic effect, steric effect and conjugation effect, make the manufactured product have better mechanical properties, better wear resistance, heat aging resistance and cold resistance, better performance stability and longer service life.
[0025] (3) The high-strength carbon fiber synchronous belt disclosed in the present invention forms an interpenetrating network structure inside the film under the action of a vulcanizing agent. At the same time, under the action of a catalyst, the acyl chloride group on 4,4-chloroformylphenyl ether can react with a structure containing a benzene ring to further increase the crosslinking density, thereby effectively improving the mechanical properties, wear resistance, heat aging resistance and cold resistance of the film, thereby extending the service life of the manufactured synchronous belt product.
[0026] (4) The high-strength carbon fiber synchronous belt disclosed in the present invention has a synchronous belt skeleton that is a binder-modified carbon fiber cord. The modified properties enhance the compatibility between the skeleton and the film, improve the performance stability, and extend the service life. DETAILED DESCRIPTION
[0027] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations. Example 1
[0028] A high-strength carbon fiber synchronous belt, comprising a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 30 parts of hydrogenated nitrile rubber, 10 parts of ethylene acrylate rubber, 20 parts of fluorinated ethylene propylene rubber, 1 part of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 2 parts of bis(1-vinyl imidazole-2-)ketone, and 3 parts of 2,4,6-trivinyl cycloboroxane , 2 parts of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2 parts of N-vinylcarbazole, 1 part of 4,4-chloroformylphenyl ether, 0.3 parts of catalyst, 3 parts of coupling agent, 10 parts of inorganic filler, 1 part of stearic acid, 1 part of antioxidant, 2 parts of vulcanizing agent, 0.3 parts of scorch retarder, and 2 parts of waste polyaromatic oxadiazole fiber; the synchronous belt skeleton is a binder-modified carbon fiber cord.
[0029] The waste polyaromatic oxadiazole fiber is obtained by recycling the waste Baodelun material provided by Jiangsu Baode New Materials Co., Ltd.; the average diameter of the waste polyaromatic oxadiazole fiber is 3 μm, and the aspect ratio is 15:1; the anti-scorch agent is the anti-scorch agent CTP; the vulcanizing agent is a mixture of benzoyl peroxide, di-tert-butyl peroxide, and diisopropylbenzene peroxide in a mass ratio of 1:1:0.8; the antioxidant is the antioxidant NBC; the inorganic filler is a mixture of white carbon black, light calcium carbonate, and graphene oxide in a mass ratio of 1:0.8:1; the particle size of the inorganic filler is 1000 mesh; the coupling agent is the silane coupling agent KH550; the catalyst is a mixture of anhydrous ferric chloride and anhydrous zinc chloride in a mass ratio of 1:1.
[0030] The hydrogenated nitrile rubber is selected from the brand Zhanber ® The hydrogenated nitrile rubber raw rubber of ZN35156; the ethylene acrylate rubber is selected from the brand Vamac produced by DuPont Company of the United States ® DP ethylene acrylate rubber raw rubber; the fluorinated ethylene propylene rubber is selected from the brand AFLAS ® 150% fluorinated EPDM raw rubber.
[0031] The preparation method of the binder-modified carbon fiber cord comprises the following steps: immersing the carbon fiber cord in a binder solution for 1 hour, taking it out and drying it to obtain the binder-modified carbon fiber cord; the binder solution is an ethanol solution of silane coupling agent KH550 with a mass percentage concentration of 3%.
[0032] A method for preparing the high-strength carbon fiber synchronous belt comprises the following steps:
[0033] Step S1, putting hydrogenated nitrile rubber, ethylene acrylate rubber and fluorinated ethylene propylene rubber into an open mill for mixing, alternately adding other raw materials, and mixing evenly to obtain a synchronous belt film;
[0034] Step S2, pasting the synchronous belt film package on the synchronous belt frame, and then placing it in a synchronous belt mold for compression molding and vulcanization, and cooling to room temperature to obtain a high-strength carbon fiber synchronous belt.
[0035] In step S2, the vulcanization temperature is 160° C., the vulcanization pressure is 10 MPa, and the vulcanization time is 30 min. Example 2
[0036] A high-strength carbon fiber synchronous belt, comprising a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 32 parts of hydrogenated nitrile rubber, 13 parts of ethylene acrylate rubber, 22 parts of fluorinated ethylene propylene rubber, 1.5 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 2.5 parts of bis(1-vinyl imidazole-2-)ketone, 3.5 parts of 2,4,6-trivinyl cycloboroxane, 1,3- 2.5 parts of bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 3 parts of N-vinylcarbazole, 1.2 parts of 4,4-chloroformylphenyl ether, 0.35 parts of catalyst, 3.5 parts of coupling agent, 12 parts of inorganic filler, 1.5 parts of stearic acid, 1.5 parts of antioxidant, 2.5 parts of vulcanizing agent, 0.35 parts of scorch retarder, 2.5 parts of waste polyaromatic oxadiazole fiber; the synchronous belt skeleton is a binder-modified carbon fiber cord.
[0037] The waste polyaromatic oxadiazole fiber is obtained by recycling the waste Baodelun materials provided by Jiangsu Baode New Materials Co., Ltd.; the anti-scorch agent is the anti-scorch agent CTP; the vulcanizing agent is a mixture of benzoyl peroxide, di-tert-butyl peroxide, and diisopropylbenzene peroxide in a mass ratio of 1:1.2:0.9; the antioxidant is the antioxidant BLE; the inorganic filler is a mixture of white carbon black, light calcium carbonate, and graphene oxide in a mass ratio of 1:0.9:1.2; the particle size of the inorganic filler is 1100 mesh; the coupling agent is the silane coupling agent KH560; the catalyst is a mixture of anhydrous ferric chloride and anhydrous zinc chloride in a mass ratio of 1.3:1.
[0038] The hydrogenated nitrile rubber is selected from the brand Zhanber ® The hydrogenated nitrile rubber raw rubber of ZN35156; the ethylene acrylate rubber is selected from the brand Vamac produced by DuPont Company of the United States ® DP ethylene acrylate rubber raw rubber; the fluorinated ethylene propylene rubber is selected from the brand AFLAS ® 150% fluorinated EPDM raw rubber.
[0039] The preparation method of the binder-modified carbon fiber cord comprises the following steps: immersing the carbon fiber cord in a binder solution for 1.5 hours, taking it out and drying it to obtain the binder-modified carbon fiber cord; the binder solution is an ethanol solution of silane coupling agent KH550 with a mass percentage concentration of 4%.
[0040] A method for preparing the high-strength carbon fiber synchronous belt comprises the following steps:
[0041] Step S1, putting hydrogenated nitrile rubber, ethylene acrylate rubber and fluorinated ethylene propylene rubber into an open mill for mixing, alternately adding other raw materials, and mixing evenly to obtain a synchronous belt film;
[0042] Step S2, pasting the synchronous belt film package on the synchronous belt frame, and then placing it in a synchronous belt mold for compression molding and vulcanization, and cooling to room temperature to obtain a high-strength carbon fiber synchronous belt.
[0043] In step S2, the vulcanization temperature is 163° C., the vulcanization pressure is 11 MPa, and the vulcanization time is 33 min. Example 3
[0044] A high-strength carbon fiber synchronous belt, comprising a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 35 parts of hydrogenated nitrile rubber, 15 parts of ethylene acrylate rubber, 25 parts of fluorinated ethylene propylene rubber, 2 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 3 parts of bis(1-vinyl imidazole-2-)ketone, 4 parts of 2,4,6-trivinyl cycloboroxane, 1 , 3 parts of 3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 3.5 parts of N-vinylcarbazole, 1.5 parts of 4,4-chloroformylphenyl ether, 0.4 parts of catalyst, 4 parts of coupling agent, 15 parts of inorganic filler, 2 parts of stearic acid, 2 parts of antioxidant, 3 parts of vulcanizing agent, 0.4 parts of anti-scorch agent, and 3 parts of waste polyaromatic oxadiazole fiber; the synchronous belt skeleton is a binder-modified carbon fiber cord.
[0045] The waste polyaromatic oxadiazole fiber is obtained by recycling the waste Baodelun material provided by Jiangsu Baode New Materials Co., Ltd.; the average diameter of the waste polyaromatic oxadiazole fiber is 5 μm, and the aspect ratio is 17:1; the anti-scorch agent is the anti-scorch agent CTP; the vulcanizing agent is a mixture of benzoyl peroxide, di-tert-butyl peroxide, and diisopropylbenzene peroxide in a mass ratio of 1:1.5:1; the antioxidant is the antioxidant NBC; the inorganic filler is a mixture of white carbon black, light calcium carbonate, and graphene oxide in a mass ratio of 1:1:1.5; the particle size of the inorganic filler is 1300 mesh; the coupling agent is the silane coupling agent KH570; the catalyst is a mixture of anhydrous ferric chloride and anhydrous zinc chloride in a mass ratio of 1.5:1.
[0046] The hydrogenated nitrile rubber is selected from the brand Zhanber ® The hydrogenated nitrile rubber raw rubber of ZN35156; the ethylene acrylate rubber is selected from the brand Vamac produced by DuPont Company of the United States ® DP ethylene acrylate rubber raw rubber; the fluorinated ethylene propylene rubber is selected from the brand AFLAS ® 150% fluorinated EPDM raw rubber.
[0047] The preparation method of the binder-modified carbon fiber cord comprises the following steps: immersing the carbon fiber cord in a binder solution for 2 hours, taking it out and drying it to obtain the binder-modified carbon fiber cord; the binder solution is an ethanol solution of silane coupling agent KH550 with a mass percentage concentration of 4.5%.
[0048] A method for preparing the high-strength carbon fiber synchronous belt comprises the following steps:
[0049] Step S1, putting hydrogenated nitrile rubber, ethylene acrylate rubber and fluorinated ethylene propylene rubber into an open mill for mixing, alternately adding other raw materials, and mixing evenly to obtain a synchronous belt film;
[0050] Step S2, pasting the synchronous belt film package on the synchronous belt frame, and then placing it in a synchronous belt mold for compression molding and vulcanization, and cooling to room temperature to obtain a high-strength carbon fiber synchronous belt.
[0051] In step S2, the vulcanization temperature is 165° C., the vulcanization pressure is 13 MPa, and the vulcanization time is 35 min. Example 4
[0052] A high-strength carbon fiber synchronous belt, comprising a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 38 parts of hydrogenated nitrile rubber, 18 parts of ethylene acrylate rubber, 28 parts of fluorinated ethylene propylene rubber, 2.5 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 3.5 parts of bis(1-vinyl imidazole-2-)ketone, 4.5 parts of 2,4,6-trivinyl cycloboroxane, 1,3-bis(1,3-diphenylene)propene, 1,2 ... 3.5 parts of (oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 4.5 parts of N-vinylcarbazole, 1.8 parts of 4,4-chloroformylphenyl ether, 0.45 parts of catalyst, 4.5 parts of coupling agent, 19 parts of inorganic filler, 2.5 parts of stearic acid, 2.5 parts of antioxidant, 3.5 parts of vulcanizing agent, 0.45 parts of anti-scorch agent, and 3.5 parts of waste polyaromatic oxadiazole fiber; the synchronous belt skeleton is a binder-modified carbon fiber cord.
[0053] The waste polyaromatic oxadiazole fiber is obtained by recycling the waste Baodelun material provided by Jiangsu Baode New Materials Co., Ltd.; the average diameter of the waste polyaromatic oxadiazole fiber is 7 μm, and the aspect ratio is 23:1; the anti-scorch agent is the anti-scorch agent CTP; the vulcanizing agent is a mixture of benzoyl peroxide, di-tert-butyl peroxide, and diisopropylbenzene peroxide in a mass ratio of 1:1.8:1.1; the antioxidant is a mixture of antioxidant NBC and antioxidant BLE in a mass ratio of 3:5 The inorganic filler is a mixture formed by mixing white carbon black, light calcium carbonate and graphene oxide in a mass ratio of 1:1.1:1.8; the particle size of the inorganic filler is 1400 mesh; the coupling agent is a mixture formed by mixing silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570 in a mass ratio of 1:3:2; the catalyst is a mixture formed by mixing anhydrous ferric chloride and anhydrous zinc chloride in a mass ratio of 1.8:1.
[0054] The hydrogenated nitrile rubber is selected from the brand Zhanber ®The hydrogenated nitrile rubber raw rubber of ZN35156; the ethylene acrylate rubber is selected from the brand Vamac produced by DuPont Company of the United States ® DP ethylene acrylate rubber raw rubber; the fluorinated ethylene propylene rubber is selected from the brand AFLAS ® 150% fluorinated EPDM raw rubber.
[0055] The preparation method of the binder-modified carbon fiber cord comprises the following steps: immersing the carbon fiber cord in a binder solution for 2.5 hours, taking it out and drying it to obtain the binder-modified carbon fiber cord; the binder solution is an ethanol solution of silane coupling agent KH550 with a mass percentage concentration of 5.5%.
[0056] A method for preparing the high-strength carbon fiber synchronous belt comprises the following steps:
[0057] Step S1, putting hydrogenated nitrile rubber, ethylene acrylate rubber and fluorinated ethylene propylene rubber into an open mill for mixing, alternately adding other raw materials, and mixing evenly to obtain a synchronous belt film;
[0058] Step S2, pasting the synchronous belt film package on the synchronous belt frame, and then placing it in a synchronous belt mold for compression molding and vulcanization, and cooling to room temperature to obtain a high-strength carbon fiber synchronous belt.
[0059] In step S2, the vulcanization temperature is 168° C., the vulcanization pressure is 14 MPa, and the vulcanization time is 38 min. Example 5
[0060] A high-strength carbon fiber synchronous belt, comprising a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 40 parts of hydrogenated nitrile rubber, 20 parts of ethylene acrylate rubber, 30 parts of fluorinated ethylene propylene rubber, 3 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 4 parts of bis(1-vinyl imidazole-2-)ketone, and 5 parts of 2,4,6-trivinyl cycloboroxane , 4 parts of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 5 parts of N-vinylcarbazole, 2 parts of 4,4-chloroformylphenyl ether, 0.5 parts of catalyst, 5 parts of coupling agent, 20 parts of inorganic filler, 3 parts of stearic acid, 3 parts of antioxidant, 4 parts of vulcanizing agent, 0.5 parts of anti-scorch agent, 4 parts of waste polyaromatic oxadiazole fiber; the synchronous belt skeleton is a binder-modified carbon fiber cord.
[0061] The waste polyaromatic oxadiazole fiber is obtained by recycling the waste Baodelun material provided by Jiangsu Baode New Materials Co., Ltd.; the average diameter of the waste polyaromatic oxadiazole fiber is 9 μm, and the aspect ratio is 25:1; the anti-scorch agent is the anti-scorch agent CTP; the vulcanizing agent is a mixture of benzoyl peroxide, di-tert-butyl peroxide, and diisopropylbenzene peroxide in a mass ratio of 1:2:1.2; the antioxidant is the antioxidant NBC; the inorganic filler is a mixture of white carbon black, light calcium carbonate, and graphene oxide in a mass ratio of 1:1.2:2; the particle size of the inorganic filler is 1500 mesh; the coupling agent is the silane coupling agent KH550; the catalyst is a mixture of anhydrous ferric chloride and anhydrous zinc chloride in a mass ratio of 2:1.
[0062] The hydrogenated nitrile rubber is selected from the brand Zhanber ® The hydrogenated nitrile rubber raw rubber of ZN35156; the ethylene acrylate rubber is selected from the brand Vamac produced by DuPont Company of the United States ® DP ethylene acrylate rubber raw rubber; the fluorinated ethylene propylene rubber is selected from the brand AFLAS ® 150% fluorinated EPDM raw rubber.
[0063] The preparation method of the binder-modified carbon fiber cord comprises the following steps: immersing the carbon fiber cord in a binder solution for 3 hours, taking it out and drying it to obtain the binder-modified carbon fiber cord; the binder solution is an ethanol solution of silane coupling agent KH550 with a mass percentage concentration of 6%.
[0064] A method for preparing the high-strength carbon fiber synchronous belt comprises the following steps:
[0065] Step S1, putting hydrogenated nitrile rubber, ethylene acrylate rubber and fluorinated ethylene propylene rubber into an open mill for mixing, alternately adding other raw materials, and mixing evenly to obtain a synchronous belt film;
[0066] Step S2, pasting the synchronous belt film package on the synchronous belt frame, and then placing it in a synchronous belt mold for compression molding and vulcanization, and cooling to room temperature to obtain a high-strength carbon fiber synchronous belt.
[0067] In step S2, the vulcanization temperature is 170° C., the vulcanization pressure is 15 MPa, and the vulcanization time is 40 min.
[0068] Comparative Example 1
[0069] A high-strength carbon fiber synchronous belt is substantially the same as Example 1, except that (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate and bis(1-vinyl imidazole-2-)ketone are not added.
[0070] Comparative Example 2
[0071] A high-strength carbon fiber synchronous belt is substantially the same as Example 1, except that 2,4,6-trivinyl cycloboroxine and N-vinyl carbazole are not added.
[0072] In order to further illustrate the beneficial technical effects of the high-strength carbon fiber synchronous belts involved in each embodiment of the present invention, relevant performance tests were performed on the high-strength carbon fiber synchronous belts involved in Examples 1-5 and Comparative Examples 1-2. The test results are shown in Table 1. The test method is as follows: the tensile strength is measured according to GB / T 10716-2012; in order to control the variables, the ratio of the skeleton thickness to the thickness of the film in each test sample is 4:21; the carbon fiber cords are all made of M55J grade high-strength and high-modulus carbon fiber; the aging resistance is to place the synchronous belt rubber of each product in hot air at 125°C for artificial accelerated aging for 70 hours, cool it to room temperature, test and calculate the retention rate of the tensile strength of the synchronous belt rubber at room temperature, the larger the retention rate, the better the heat aging resistance, and the rubber tensile strength test refers to GB / T 528-2009, with a tensile rate of 100mm / min; the low temperature resistance performance is achieved by placing the synchronous belt rubber of each product at -40℃ for 5 hours, then returning to room temperature, testing and calculating the retention rate of the tensile strength of the synchronous belt rubber at room temperature. The larger the retention rate, the better the cold resistance performance. The tensile strength test of the rubber is carried out with reference to GB / T528-2009, with a tensile rate of 100mm / min; Akron abrasion is measured according to GB / T1689-1998.
[0073] Table 1
[0074] project Tensile Strength Heat aging resistance cold resistance Axlon Wear unit N / mm % % <![CDATA[cm 3 ·(1.61km) -1 ]]> Example 1 2100 98.67 98.92 0.0023 Example 2 2100 98.74 99.01 0.0020 Example 3 2200 98.84 99.20 0.0014 Example 4 2200 98.90 99.35 0.0011 Example 5 2300 98.95 99.58 0.0010 Comparative Example 1 2000 95.68 96.23 0.0088 Comparative Example 2 2000 95.92 96.57 0.0076
[0075] As can be seen from Table 1, the high-strength carbon fiber synchronous belt disclosed in the embodiment of the present invention has better mechanical properties, heat aging resistance, cold resistance and wear resistance than the comparative example product, and the addition of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, bis(1-vinylimidazole-2-)ketone, 2,4,6-trivinylcycloboroxane and N-vinylcarbazole is beneficial to improving the above properties.
[0076] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A high-strength carbon fiber synchronous belt, characterized in that: The invention comprises a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 30-40 parts of hydrogenated nitrile rubber, 10-20 parts of ethylene acrylate rubber, 20-30 parts of fluorinated ethylene propylene rubber, 1-3 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 2-4 parts of bis(1-vinyl imidazole-2-)ketone, 3-5 parts of 2,4,6-trivinyl cycloboroxane, 1,3-bis(ethylene oxide) methyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione 2-4 parts, N-vinyl carbazole 2-5 parts, 4,4-chloroformyl phenyl ether 1-2 parts, catalyst 0.3-0.5 parts, coupling agent 3-5 parts, inorganic filler 10-20 parts, stearic acid 1-3 parts, antioxidant 1-3 parts, vulcanizing agent 2-4 parts, anti-scorch agent 0.3-0.5 parts, waste polyaromatic oxadiazole fiber 2-4 parts; the synchronous belt skeleton is a binder modified carbon fiber cord.
2. The high-strength carbon fiber synchronous belt according to claim 1, characterized in that: The average diameter of the waste polyaromatic oxadiazole fiber is 3-9 μm, and the aspect ratio is (15-25):
1.
3. The high-strength carbon fiber synchronous belt according to claim 1, characterized in that: The anti-scorch agent is anti-scorch agent CTP; the vulcanizing agent is a mixture formed by mixing benzoyl peroxide, di-tert-butyl peroxide and diisopropylbenzene peroxide in a mass ratio of 1:(1-2):(0.8-1.2).
4. The high-strength carbon fiber synchronous belt according to claim 1, characterized in that: The antioxidant is at least one of antioxidant NBC and antioxidant BLE; the inorganic filler is a mixture of white carbon black, light calcium carbonate and graphene oxide in a mass ratio of 1:(0.8-1.2):(1-2); the particle size of the inorganic filler is 1000-1500 mesh.
5. The high-strength carbon fiber synchronous belt according to claim 1, characterized in that: The coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570; the catalyst is a mixture of anhydrous ferric chloride and anhydrous zinc chloride in a mass ratio of (1-2):
1.
6. The high-strength carbon fiber synchronous belt according to claim 1, characterized in that: The hydrogenated nitrile rubber is selected from the brand Zhanber ® The hydrogenated nitrile rubber raw rubber of ZN35156; the ethylene acrylate rubber is selected from the brand Vamac ® DP ethylene acrylate rubber raw rubber; the fluorinated ethylene propylene rubber is selected from the brand AFLAS ® 150% fluorinated EPDM raw rubber.
7. The high-strength carbon fiber synchronous belt according to claim 1, characterized in that: The method for preparing the binder-modified carbon fiber cord comprises the following steps: immersing the carbon fiber cord in a binder solution for 1-3 hours, taking it out and drying it to obtain the binder-modified carbon fiber cord.
8. The high-strength carbon fiber synchronous belt according to claim 7, characterized in that: The binder solution is an ethanol solution of silane coupling agent KH550 with a mass percentage concentration of 3-6%.
9. A method for preparing the high-strength carbon fiber synchronous belt according to any one of claims 1 to 8, characterized in that: The steps include: Step S1, putting hydrogenated nitrile rubber, ethylene acrylate rubber and fluorinated ethylene propylene rubber into an open mill for mixing, alternately adding other raw materials, and mixing evenly to obtain a synchronous belt film; Step S2, pasting the synchronous belt film package on the synchronous belt frame, and then placing it in a synchronous belt mold for compression molding and vulcanization, and cooling to room temperature to obtain a high-strength carbon fiber synchronous belt.
10. The method for preparing a high-strength carbon fiber synchronous belt according to claim 9, characterized in that: In step S2, the vulcanization temperature is 160-170° C., the vulcanization pressure is 10-15 MPa, and the vulcanization time is 30-40 min.
Citation Information
Patent Citations
High performance carbon fiber synchronous belt and preparation method thereof
CN116262848B
High-performance carbon fiber synchronous belt and preparation method thereof
CN116262848A
Detention network
DE202019102091U1